2021
DOI: 10.1038/s41598-021-81526-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability and reproducibility study of radiomic features on a phantom and human cohort

Abstract: The repeatability and reproducibility of radiomic features extracted from CT scans need to be investigated to evaluate the temporal stability of imaging features with respect to a controlled scenario (test–retest), as well as their dependence on acquisition parameters such as slice thickness, or tube current. Only robust and stable features should be used in prognostication/prediction models to improve generalizability across multiple institutions. In this study, we investigated the repeatability and reproduci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 27 publications
(39 reference statements)
0
44
0
1
Order By: Relevance
“…The radiomic features of PET and CT images were selected by the following procedure. Intraclass correlation coefficient (ICC > 0.75) was first performed to remove the redundant features (25,26). Subsequently, the retained features were further selected by the least absolute shrinkage and selection operator (LASSO) regression algorithm (27).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…The radiomic features of PET and CT images were selected by the following procedure. Intraclass correlation coefficient (ICC > 0.75) was first performed to remove the redundant features (25,26). Subsequently, the retained features were further selected by the least absolute shrinkage and selection operator (LASSO) regression algorithm (27).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…A total of 15 patients were randomly selected to calculate the interobserver agreement of the feature extraction. e intraclass correlation coefficient (ICC) was used to determine the repeatability/reproducibility of features in our research, and ICC >0.75 was selected [24][25][26]. Subsequently, the least absolute shrinkage and selection operator (LASSO) COX regression model was used to select the most useful prognostic features with 10-fold cross validation for selecting the parameter Lambda in the training cohort [27,28] (adriamycin, bleomycin, vinblastine, and dacarbazine).…”
Section: Feature Extraction and Selectionmentioning
confidence: 99%
“…Robustness of radiomic features relies on reproducibility and repeatability of their estimates considering different aspects of the radiomic workflow [ 19 , 20 ]. Previous studies of CT imaging [ 21 24 ], as well as of MR [ 25 30 ] and NM [ 31 34 ] imaging, have assessed the reproducibility and repeatability of radiomic features estimation for various applications. Phantom and in vivo CT studies have reported dependence of radiomic feature estimates on various factors such as scanner type [ 35 , 36 ], tube current [ 37 39 ], acquisition voxel size [ 21 , 35 ], reconstruction kernel [ 40 43 ], and number of gray levels [ 21 ] or gray level discretization [ 35 ].…”
Section: Introductionmentioning
confidence: 99%